O experimento do balde de Newton sob a interpretação da mecânica newtoniana e da mecânica relacional - Sousa, Luciana Vital Dantas (2021)
In his most important work, Mathematical Principles of Natural Philosophy, Isaac Newton introduced the notion of absolute space as an ideal condition so that his movement axioms could be applied in a logical and rigorous way. Thus, in the Newtonian universe, absolute space can be understood as the stage on which the movement takes place, which Newton sought to demonstrate with the experience of the spinning bucket and the effects observed in circular movements. In this text, the proposal was to present the criticisms of newton's notion of absolute space by philosophers such as Leibniz and Berkeley, already in the early seventeenth century, and later Ernst Mach and his relational ideas, from the perspective of Relational Mechanics with the contributions of André Koch Torres Assis. Itis noteworthy that the scenario of this work brings Newtonian Mechanics as the stage through which the research is carried over, having the experience of Newton's bucket as the protagonist, with the objective of contributing with a reflexive critique on the foundations of Newtonian formalism. The aim was to deepen the reflections on the references and present alternatives to the traditional methods of interpretation of events by Classical Mechanics, without intending to abandon ideas, but to seek alternatives to the established perspectives, providing subsidies for reflexive criticism in the classroom in the teaching of science. Thus, epistemologically, this research brings the innovative posture of Paul Feyeraband, highlighting the reflection on the fundamentals of physics from the perspective of two distinct theories: Classical Mechanics and Relational Mechanics. Thus, in the conception of science teaching, the rescue of history and philosophy was provided with its foundations, through virtual meetings with workshops and lives, as well as from the results of the application of specific questionnaires to the participants in order to identify the individual knowledge about the theories that allow understanding the observed events. At the end of this work, we conclude that the interpretation of the utterances of Newton's bucket experience, either through Newtonian Mechanics or relational mechanics, with its consequent pronouncements and its problems, provided the participants with a change in their conceptions related to the foundations of theories that contemplate the interpretations of the movement of bodies under a given referential.